2023
DOI: 10.34172/ija.2023.e15
|View full text |Cite
|
Sign up to set email alerts
|

Road Safety as an Essential Need of Aged Population: A Case of Tabriz City, Iran

Mahsa Fathi,
Ali Ahmadinia,
Nader Pourhassan
et al.

Abstract: Objectives: To investigate and determine the hotspot points of traffic accidents in the Tabriz metropolis during 2020-2021. Design: Cross-sectional descriptive study. Setting(s): Tabriz, Capital of East Azarbaijan province in northwest Iran. Participants: The patients were injured in traffic accidents and transferred to hospitals with the prehospital system in Tabriz in 2020 and 2021. Interventions: Prehospital ambulances. Outcome measures: The data included the number of traffic accidents, demographic variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Elevated ratios can strain government spending, leading to challenges such as labor shortages, increased healthcare costs, potential decreases in overall quality of life, and road safety issues. 1 As Vietnam progresses into stage 4 of the DTM, the base of the population pyramid is expected to narrow due to low birth rates, resulting in a top-heavy structure with a broader top, as depicted in Figure 2 (2050 population pyramid). This shift indicates population aging, measured by the ratio of people above 65 years old to the total population, indicating the share of older individuals in society.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated ratios can strain government spending, leading to challenges such as labor shortages, increased healthcare costs, potential decreases in overall quality of life, and road safety issues. 1 As Vietnam progresses into stage 4 of the DTM, the base of the population pyramid is expected to narrow due to low birth rates, resulting in a top-heavy structure with a broader top, as depicted in Figure 2 (2050 population pyramid). This shift indicates population aging, measured by the ratio of people above 65 years old to the total population, indicating the share of older individuals in society.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that other countries experience this phenomenon in the future. After the last census, the results of the forecasts showed that with any possible scenario, Iran would face population aging [2]. In aging, there are challenges such as loneliness [3], changing relationships and social roles [4], chronic illness, and the death of spouses and friends [5].…”
Section: Introductionmentioning
confidence: 99%
“…The world population is aging. Like other countries, Iran is also facing population aging [2]. Certainly, aging will have consequences that can be considered.…”
Section: Introductionmentioning
confidence: 99%